EFEKTIVITAS MEDIA INTERAKTIF WORDWALL TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA PADA MATERI RASIO DI KELAS VI SD - Saniah Widya, Nur; Nirvi Lestari , Adinda; Fajri, Ahmad; Murni, Anggia; Alviannor , Muhammad; Maimunah; Suriansyah, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the interactive learning media Wordwall in enhancing students’ learning motivation in the topic of ratios among sixth grade students at SD. The background of this research stems from the low levels of interest and motivation among students in mathematics learning, which tends to be monotonous and teacher centerer. The use of Wordwall is also expected to create a more engaging and interactive learning environment, encouraging the students’ active participation through a gamification based approach. This research employed a quantitative descriptive method involving 32 sixth-grade students and one teacher as research subjects. Data were collected through observation, questionnaires, and interviews, and analyzed using a triangulation method to validate findings from multiple sources. The results indicate that the use of Wordwall effectively increases students’ motivation, creativity, and competitive spirit. Based on these findings, this study recommends that Wordwall to be implemented in elementary schools as an innovative and effective learning tool to prevent student boredom during lessons.